Kłopotliwe spotkanie ("Ziemia" Adama Wiedemanna) - Jaworski, Marcin (My University, 2012)
The poem is interpreted as an ironic self-thematic commentary. The poet’s attitude is critical towards different interpretations: conventional, i.e. based on ambiguity, colloquial or stereotypical and academic, inspired by increasingly new theories. The substantial element in the poem is the relation between the subject (persona) and the protagonist that corresponds to and translates into a communicative situation between the author and the reader. The result is complex, intertwined styles and techniques combined with one another. Wiedemann engages in a play with different ways of writing, ironically challenges or undermines poetical strategies to underline the conventionality of literature and communication in general. By doing this, he disturbs the reader by challenging the reader’s reading habits and thus making an impression that the reader is sent away from the poem to a single and unique experience in reality.
A perplexing encounter (The poem “Ziemia” by Adam Wiedemann)
Keywords: poetry of Adam Wiedemann; self-thematic literature; poetry and literary criticism; literature and ethics; everyday life in poetry; Marjorie Perloff